The modeling and forecasting of prevalence of dependence on psychoactive substances - Linskiy, I. V.; Tolstoluzhskiy, D. A.; Barannik, E. A. (Biophysical Bulletin)
Based upon the approaches of population ecology the analysis of dynamics of proliferation of substance abuse in Ukraine was carried out. It is offered the modified model of Verhulst allowing to describe and predict mentioned above dynamics on the basis of available official data of medical statistics. By approximation of available statistical data numerical parameters of model are established and conclusions concerning the greatest possible number of alcohol and drugs addicted persons in Ukraine are drawn. Ways of the further development of the developed model taking into account all factors influencing process of proliferation of substance abuse are discussed.